Active Arabic Learning Strategies In Improving Language Skills - Siswanto, Nopri Dwi (UIN Sunan Gunung Djati Bandung, 2022)
Arabic learning has complex problems, including monotonous and boring learning methods, so teachers must be able to innovate to create active, practical, and fun Arabic learning. So that this study aims to explain how active Arabic learning strategies improve language skills. Active learning strategies have a critical role in achieving learning objectives. With active learning strategies, the learning process will be fun and can reduce student boredom while studying. The right strategy can affect student learning outcomes. The research approach used in this study is qualitative. The type of research is Library Research. This research uses descriptive qualitative analysis. The results of this study can be concluded that when a teacher can mix strategies in teaching, students will be able to learn in various ways. Students with audio, visual, and kinesthetic types of learning will be accommodated if the learning strategies are well mixed. When the type of student learning has been met, they will feel different nuances in learning, and learning objectives will undoubtedly be easy to achieve.